A trait‐based ecosystem model suggests that long‐term responsiveness to rising atmospheric CO2 concentration is greater in slow‐growing than fast‐growing plants. (7th June 2013) - Ali, Ashehad A.; Medlyn, Belinda E.; Crous, Kristine Y.; Reich, Peter B.
Summary: Atmospheric carbon dioxide concentration ( C a ) has a direct and measurable effect on plant growth. However, it does not affect all plant species equally, which could lead to shifts in competitive dominance of species in ecosystems. We used a dynamic plant carbon–nitrogen model to systematically examine how species traits affect the long‐term C a responsiveness of C3 plants when growing as established monocultures in the field. The model was tested against responses of 7 C3 herbaceous species growing in a free‐air C a enrichment (FACE) experiment (BioCON) in Minnesota, USA. Model simulations showed that several species traits affected the C a response strongly, giving rise to a number of testable hypotheses about interspecific differences in responsiveness to C a . The largest responses to rising C a were obtained for species with low carbon‐use efficiency (net primary production: gross primary production ratio), low foliar carbon allocation, low stomatal conductance, low instantaneous photosynthetic nitrogen use efficiency and low specific leaf area. In general, our model predicted that, for established plants growing in resource‐limited field conditions, species with slow growth rates would be most responsive to elevated C a . This prediction was supported by data from the BioCON experiment. Our model also predicts that, for young plants growing in non‐resource‐limited conditions, species with high growth rates will be most responsive to elevated C a . This difference in species ranking under different resource availabilities is largely explained by the indirect effects of C a on leaf area. Leaf‐area feedbacks favour fast‐growing species the most during leaf‐area expansion, but following stand maturation they favour slow‐growing species the most. These results imply that species that respond strongly to elevated C a in short‐term (non‐resource‐limited) glasshouse experiments are unlikely to also be the most responsive in resource‐limited field conditions, and therefore that we cannot directly extrapolate from glasshouse experiments to predict which species will be most responsive to elevated C a in the long term. Abstract : Lay Summary Abstract :